Sergiusz Hessen jako publicysta „Kultury i Wychowania” w latach 1933–1939 - Boczoń, Magdalena Lidia (Biuletyn Historii Wychowania, 2011)
The specific character of the interwar period promoted the development of specialist magazines, among others, also magazines from the field of pedagogy. Those periodicals published discussions and disputes which were a creative contribution of Polish thinkers, scholars and teachers-practicians into the process of the restoration of Poland by means of improving the quality of educational activities. Kultura i Wychowanie (“Culture and Education”) was one of such magazines which owed its high specialist level mainly to its chief editor – Bogdan Suchodolski. Kultura i Wychowanie attracted a number of eminent authors, including Sergiusz Hessen. The presented article focuses on the works of this Russian pedagogue published in the discussed magazine and, first of all, his contribution into the construction of the theoretical foundations of the Polish pedagogy of culture from the period of the Second Polish Republic. The articles of Hessen, published in B. Suchodolski’s periodical, were an elaboration of the philosophy which the author presented earlier in his book Podstawy pedagogiki (“The Foundations of Pedagogy”). They were also preparatory considerations to his subsequent book entitled O sprzecznościach i jedności wychowania (“On Contradictions and Unity of Education”). The subjects of these articles concern two areas: the essence and meaning of Weltanschaung and the role of the concept of general education. The author of the article specifies in S. Hessen’s works published in the magazine Kultura i Wychowanie a number of ideas and concepts which contributed to the formation of the theoretical foundations of the Polish pedagogy of culture in the interwar period. They included: – a concept of a teacher fulfilling a role of a liberating authority; the liberating and upbringing education; the idea of “acquiring” personality via “acquiring” one’s own Weltanschaung; a constant tension between community and individualism; co-creation of culture by individual people as the main factor of its development; the manifestation of the layers of existence at the subsequent stages of education.